Microbiota and Alzheimer’s disease: toward new clinical approaches - Djokić, Jelena; Dinić, Miroslav (Medicinski podmladak, 2025)
Alzheimer’s disease (AD) is now viewed as a systemic disorder in which genetics, the gut microbiome and immune dysregulation converge to accelerate amyloid-β (Aβ) and tau pathology. Genetic studies have identified 70 risk loci. APOE ε4 is the strongest AD risk loci, conferring dose-dependent risk through impaired cholesterol trafficking, reduced Aβ clearance and heightened neuroinflammation. Rare mutations in TREM2 and CD33 further illustrate the centrality of microglia-mediated innate immunity. Importantly, peripheral Th17 skewing, neutrophil hyper-activation and loss of regulatory myeloid cells amplify neuroinflammation. Growing evidence links gut dysbiosis to these genetic factors. APOE ε4 carriers show depletion of Short-Chain Fatty Acids (SCFA)-producing taxa (Gemmiger, Roseburia, Faecalibacterium) and enrichment of pro-inflammatory Proteobacteria (Escherichia/Shigella, Morganella). In mice, APOE4-dependent loss of butyrate-producing bacteria lowers colonic and serum SCFA levels and worsens tauopathy, whereas Germ-free housing, early antibiotics and SCFA supplementation rescue pathology. Large meta-analyses correlate Collinsella and Veillonella with higher AD risk, and Eubacterium nodatum and Prevotella 9 with protection. Metabolomic shifts mirror these compositional changes: acetate, propionate and butyrate, as well as trimethylamine N-oxide (TMAO) promote epigenetic regulation, blood–brain-barrier (BBB) integrity and microglial homeostasis, whereas secondary bile acids compromise cognition. The microbial amyloids and lipopolysaccharide can cross-seed Aβ, activate the NLRP3 inflammasome, and breach the blood-brain barrier. Intermittent fasting, ketogenic diets, specific probiotics (Bifidobacterium breve A1, Lacticaseibacillus rhamnosus CBT-LR5), sodium oligomannate (GV-971) or fecal microbiota transplantation can remodel gut ecology, raise beneficial SCFAs, dampen pro-inflammatory cytokines and improve cognition in patients with AD or mild cognitive impairment. Collectively, the data support a gut–immune system-brain axis in which host genotype shapes microbiota, and microbial metabolites or antigens contribute to neurodegeneration. Future work must define responder phenotypes, optimise next-generation probiotics and integrate multi-omics profiling with biomarker-driven clinical trials to translate microbiota modulation into disease-modifying therapy for AD.
Keywords: Alzheimer’s Disease, APOE, Neuroinflammation, Microbiota, Short-chain fatty acide, Probiotics